Mesin Pengisian Cairan Otomatis Menggunakan Arduino dan LabVIEW - Syafriyadi Nor; Zaiyan Ahyadi (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2025)
The automatic liquid-filling machine plays a vital role in improving efficiency and productivity in modern manufacturing and packaging industries. However, challenges such as high costs, complexity, and limited technical knowledge often hinder its adoption. This research aimed to develop an educational system that is simple, affordable, and easy to implement, helping students grasp the fundamental principles and real-world applications of automatic liquid-filling machines. The system integrates LabVIEW for visual processing and an Arduino Nano microcontroller with the Modbus remote terminal unit (RTU) protocol to simulate industrial communication standards. LabVIEW controls the conveyor belt, filling, and capping processes using ladder logic while recording the number of filled bottles. The Arduino microcontroller manages conveyor belt operations and allows users to set volume and bottle count via a keypad. Serial communication between LabVIEW and Arduino through Modbus RTU provides hands-on experience in configuring industrial systems. Experimental tests under various operational scenarios confirmed the system’s accuracy in filling bottles within a volume range of 250–1,000 ml at a speed of 10 ml/s, handling up to five bottles per cycle. The system demonstrated stable operation without disruptions. This research enhances instrumentation and control system education by offering an interactive, cost-efficient learning tool. The successful use of Modbus RTU underscores its reliability in supporting automatic liquid-filling machines while enriching students’ understanding of industrial automation.